2011
DOI: 10.1007/s10195-011-0139-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral impaction of the posterior acetabular surface without cortical fracture of any wall or column: an undescribed pattern of acetabular injury

Abstract: Surgical treatment of a unusual acetabular fracture is described. This fracture was characterized by impaction and breaking down of the posterior articular surface and comminution of lamina quadrilatera lower portion, without cortical fracture of both columns. The fracture was treated surgically through the Kocher–Langenbeck approach. A small hole was created in the acetabulum posterior wall, the impacted fragment was reduced, and the bone defect was filled with autologous bone from the greater trochanter. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The technique is useful only when fracture involves the Q surface. Recently, Pascarella et al [40] reported an undescribed pattern of acetabular injury. There was osteochondral impaction of the posterior acetabular surface without cortical fracture of any wall or column.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is useful only when fracture involves the Q surface. Recently, Pascarella et al [40] reported an undescribed pattern of acetabular injury. There was osteochondral impaction of the posterior acetabular surface without cortical fracture of any wall or column.…”
Section: Discussionmentioning
confidence: 99%
“…In another case reported by Pascarella et al an impacted fracture of the posteroinferior articular surface of the acetabulum with comminution of the quadrilateral lamina and fracture of the ischial bone has been discussed. In their case anterior and posterior columns were intact (12). This case also cannot be classified using the commonly used classification systems.…”
Section: Discussionmentioning
confidence: 99%
“…have reported an isolated quadrilateral plate fracture of the pelvis with no involvement of either column but with an impaction fracture of the femoral head, which also cannot be classified according to the commonly used classification systems ( 11 ).In another case reported by Pascarella et al an impacted fracture of the posteroinferior articular surface of the acetabulum with comminution of the quadrilateral lamina and fracture of the ischial bone has been discussed. In their case anterior and posterior columns were intact ( 12 ). This case also cannot be classified using the commonly used classification systems.…”
Section: Discussionmentioning
confidence: 99%
“…Once the decision to operate has been made, the operative technique, open or laparoscopic surgery, must be decided. The laparoscopy is most often recommended during the first two trimesters, as alternative diagnoses can be evaluated in case of normal appendix [ 9 - 14 ]. During the third trimester, guidelines are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…During the third trimester, guidelines are less clear. Many speak for the open approach, especially after the 26 th -28 th week of amenorrhea, but an increasing number of publications now report series of successful laparoscopic appendectomies during the third trimester [ 7 , 9 , 10 , 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%